The effect of verbal problem-solving instruction on students' structuring, acquisition and retention of knowledge - Ahmad Shah, Aliah; Roslan, Samsilah; Ghiami, Zeinab; Konting, Mohd Majid; Abu, Rosini (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This study aimed to examine the effects of teaching verbal problem-solving instruction on students' structuring, acquisition and retention of knowledge in methods of cooking. The study has been carried out on 148 students from two classes each of catering technology (n=77) and food management (n=71). Each class was randomly assigned to an experimental and a control group. Ten treatments of teaching using verbal problem-solving were given for the duration of 40 minutes of classroom teaching for four weeks. Parallel achievement tests were used to demonstrate the amount of knowledge acquired and retained after the treatment. A concept mapping test was used to assess the knowledge structure before and after the treatment. A delayed post-test of retention of knowledge was given after nine weeks of lapse after the treatment. The findings have shown that verbal problem-solving teaching has significantly increased the students' structuring, acquisition and retention of knowledge.